The Role of Social Media in the Formation of Global Cultural Identity - Yolanda, Agnita; Andary, Ria Wuri; Tamsil, Ilma Saakinah; Zaman, Khalil; Wei, Sun (Journal of Social Science Utilizing Technology, 2025)
Background. In the contemporary digital era, social media platforms have become a dominant force in shaping cultural identities across the globe. The rapid dissemination of information and interactive communication fostered by platforms such as Instagram, TikTok, Twitter, and Facebook has significantly contributed to the formation of a shared global cultural identity. Purpose. This research explores the role of social media in influencing cultural perceptions, values, and behaviors among diverse communities. The primary objective of this study is to analyze how social media facilitates cultural exchange and contributes to the convergence of cultural norms, while also highlighting the tensions between global and local identities. Method. This study adopts a qualitative approach using content analysis and semi-structured interviews involving 30 active social media users from different cultural backgrounds. Data were analyzed thematically to identify recurring patterns and narratives regarding cultural identity construction. Results. The findings reveal that social media functions both as a platform for cultural homogenization and as a space for cultural hybridity. While global trends and popular content promote a sense of shared identity, users also reinterpret and adapt these influences to fit their local cultures, resulting in the emergence of hybrid cultural expressions. Moreover, the study indicates that social media plays a crucial role in youth identity formation and in promoting cross-cultural understanding. Conclusion. In conclusion, social media acts as a double-edged sword—supporting the development of a global cultural identity while preserving unique cultural elements. Future studies are recommended to further explore this dynamic in different regional contexts.